Effect of Blood Viscosity Variation on the Flow of Blood in an Artery Having Time Dependent Stenosis (Contemporary Mathematics, 2023)
The aim of this paper is to examine the impact of blood viscosity variation on the flow of blood in a diseased artery having time-dependent stenosis. The viscosity of blood is axial co-ordinate dependent so that the viscosity of the blood increases up to the highest point of stenosis in the whole artery after which it decreases. Analytical methods have been used to explore the problem. The equations of volumetric rate of flow, resistance to flow, wall shear stress, and axial velocity have been obtained. It is noticed that as stenosis height increases, the resistance to flow and the wall shear stress increases. Also, investigation has been done to investigate how the wall sheer stress and flow resistance vary with different time-related parameters and varying viscosity index values.
Keywords: volumetric flow rate; blood flow; wall shear stress; time dependent stenosis